Flouting Maxim in He’s All That Movie - Komang Dian Puspita Candra; Ni Putu Ira Suartini (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
This research discuss flouting maxim found in He's All That movie. The purpose of this research is to determine the types of maxim that flouted by the whole characters in the movie. The data collecting was conducted by observation method. The technique for collecting data is by watching the movie for many times. Then, taking notes the utterances spoken by the characters, and categorized the scripts into types of flouting maxim. After that, the data were analyzed using the descriptive qualitative method. The researcher applied Grice’s theory to conduct this research. The findings showed that all the types of maxim were flouted by the characters in He's All That movie. The first is flouting maxim of quantity, second is flouting maxim of quality, third is flouting maxim of relevance, and fourth is flouting maxim of manner. Flouting maxim of quantity is the most often appears. The characters clearly give less or more information than is necessary in He’s All That movie. In addition, the characters give more information because they want to strengthen the information given to the interlocutor. Then, they want the interlocutor to understand the topic despite their lack of information.